Pendampingan Pembuatan Legalitas Usaha melalui Online Single Submission Pada UMKM di Kelurahan Blitar - Chairunnisa, Adhila; Almas Agung Firdaus; Andini Cevia Masita; Laksmi Diana, S.S, M.Pd; Muhammad Farhan (EDUPEDIA Publisher, 2022)
Business legality is approval for conducting business activities who given to individuals or groups of people from the authorities. One form of business legality is the NIB (Business Identification Number). The existence of an NIB can provide benefits for entrepreneurs, especially when it comes to getting help from the government. There are still UMKM that don't know or receive an NIB certificate, become the main problem that is often found in the Blitar Village. This community service program aims to: given understanding, training, and business legal assistance in the form of NIB online through the Online Single Submission (OSS) application to UMKM in the Blitar Village. UMKM D'Celvin become a target in the NIB formation program. The methods used in this mentoring program are Research, Action, and Participation. The result of this assistance is that UMKM D'Celvin has knowledge about NIB, get NIB certificate, which can then be used to develop their business, such as applying for people's business loans (KUR) and guidance from the government.